Kejadian stunting pada balita usia 12-59 bulan di Desa Serule Kecamatan Bintang Kabupaten Aceh Tengah - Neni Ekowati Januariana; Tuty Hertati Purba; Agnes Sry Vera Nababan; Simah Bengi (Journal of Pharmaceutical and Sciences, 2023)
Stunting is a condition of toddlers with less length or height compared to age as measured by length or height that is more than <-2 SD of child growth, according to the World Health Organization (WHO). This study aimed to determine the factors affecting stunting in children aged 12-59 months in Serule Village, Bintang District, Central Aceh Regency. This is analytic observational research with a cross-sectional approach. The statistical test used the chi-square test. The population was 48 toddlers, all sampled by total sampling technique. I indicated a relationship between maternal knowledge and the occurrence of stunting in toddlers with a p-value = .002. There was a relationship between infectious diseases and the occurrence of stunting toddlers with a p-value = .001. There was a relationship between sanitation and the occurrence of stunting toddlers with p = .004. There was a relationship between LBW and the occurrence of stunting toddlers with a p-value = 0.000. There is a relationship between exclusive breastfeeding and stunting in toddlers with p = 0.000. There was a relationship between food intake and the occurrence of stunting in toddlers with p = .001. Conclusion of this study It is expected that mothers of toddlers pay more attention to their health, maintain environmental hygiene, fulfill their food intake, and only give breast milk when they are 0-6 months old.